Fiscal Balance, Aging Society and Migration Flow in European Union - Mega Nisfa Makhroja; Lina Trisonia; Melisa Indriana Putri (Hasanuddin University, 2023)
This study seeks to analyze the positive impact of the presence of migrant workers in developed countries which encourages fiscal balance. Over the past few decades, developed countries, including the European Union, have experienced a grey population so that the number of Labor Force has decreased. On the other hand, the European Union is obliged to pay the money of retired people. These vacancies can be filled by migrant workers. The issue of the migration crisis affecting the European Union should not be addressed negatively because refugees and migrant workers are two different forms of migration. Refugees are closely related to the issue of human security while migrant workers are one of the drivers of economic factors. The strong migration flow of workers from developing countries to the European Union encourages economic turnover and has an impact on the substitution of reduced income due to ageing society. This research uses the concepts of Fiscal balance, Ageing Society and Neo Classical Economic Migration theory to explain the European Union's efforts to maintain its Fiscal policy amid the ageing population issue that hits through the migration flow of workers to the European Union. Finding of this paper is migration and integration policy in the EU contribute to more positive fiscal balance by applying social security for a migrant in the EU.